A sonoridade do mundo como lugar da constituição da identidade - Lacerda, Regio (2009)
The research conducted here is within the scope of a qualitative research as a thesis and assumes that "the constitution of identity and his permanent transformation takes place in the context of relations with the world, with others and with oneself. The sonority as a key aspect of the world and how their dynamic is experienced has great importance in the formation of identity as well as in interpersonal relationships established therein." The identity here is taken as a whole where the individual and the collective are linked intrinsically without any possibility of understanding one aspect in isolation. The approach taken in this paper departs from the objectifying and subjectivizing positions of the identity as well as the traditional definitions of personality. The sonority is very important in the constitution of identity in that its momentum is evident in the various ways of attitudes that man takes in his involvement as the world of sound. In this sense, the involvement with the sonority momentum implies the stability of the relation-transformation that is characteristic of identity. The qualitative research was employed here as the existential approach that guides and grounds to the study. To achieve this purpose the phenomenological method was employed. This method is defined as consisting of reduction, understanding, followed by a description of the phenomenon. The testimony and semistructured interviews were the instruments used for making the speeches of selected individuals. A comprehensive reading of his speeches led us to the explanation of how the constitutive aspects of their identities are shown